2012
DOI: 10.1111/j.1574-6941.2012.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

The mercury resistance (mer) operon in a marine gliding flavobacterium,Tenacibaculum discolor9A5

Abstract: Genes conferring mercury resistance have been investigated in a variety of bacteria and archaea but not in bacteria of the phylum Bacteroidetes, despite their importance in many environments. We found, however, that a marine gliding Bacteroidetes species, Tenacibaculum discolor, was the predominant mercury‐resistant bacterial taxon cultured from a salt marsh fertilized with mercury‐contaminated sewage sludge. Here we report characterization of the mercuric reductase and the narrow‐spectrum mercury resistance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…However, the results in this paper demonstrate for the first time the significant presence of this group in the prokaryotic community of metal contaminated seawater. Flavobacteriacea was also a major component of the microbial community in strongly disturbed and metal-contaminated environments (Allen et al 2013;Wang et al 2015;Zouch et al 2018;Coclet et al 2019). Finally, the previous observation that Tenacibaculum and Formosa genera are positively selected in Cu-amended 6ext water as abundant and representative taxa from the most contaminated site 6extduring a one-month-long survey, is in agreement with the idea of a similar selective pressure in situ as that observed in our previous field study experiment (Coclet et al 2019).…”
Section: Copper Exposure Induced Changes In Prokaryotic Communitysupporting
confidence: 89%
“…However, the results in this paper demonstrate for the first time the significant presence of this group in the prokaryotic community of metal contaminated seawater. Flavobacteriacea was also a major component of the microbial community in strongly disturbed and metal-contaminated environments (Allen et al 2013;Wang et al 2015;Zouch et al 2018;Coclet et al 2019). Finally, the previous observation that Tenacibaculum and Formosa genera are positively selected in Cu-amended 6ext water as abundant and representative taxa from the most contaminated site 6extduring a one-month-long survey, is in agreement with the idea of a similar selective pressure in situ as that observed in our previous field study experiment (Coclet et al 2019).…”
Section: Copper Exposure Induced Changes In Prokaryotic Communitysupporting
confidence: 89%
“…In conclusion, our study suggested that the pool of merA loci among the arctic bacterial assemblages was diverse, mobile and represents both evolutionary recent and ancient lineages in the MerA phylogeny. The SOK62 merA gene was found to be part of an early mer operon in an isolate of the Bacteroidetes , a phylum where mercury resistance has only recently been described (Allen et al ., ). A phylogenetic analysis of this sequence together with other putative merA loci from Bacteroidetes suggested these loci to represent an early lineage in the mer phylogeny.…”
Section: Discussionmentioning
confidence: 97%
“…5). A recent study reported the mercury resistance of a member of Tenacibaculum from marine Flavobacteriaceae (67). Moreover, flavobacteria made up 70% of a Cdresistant bacterial community in soil amended with sewage sludge (68) and have not been extensively studied but could be major components of the bacterial community in metal-polluted marine environments (67).…”
Section: Discussionmentioning
confidence: 99%